Financial precarity, food insecurity, and psychological distress prospectively linked with use of potentially dangerous dietary supplements during the pandemic in the US - S. Bryn Austin; S. Bryn Austin; S. Bryn Austin; Ariel L. Beccia; Amanda Raffoul; Amanda Raffoul; Destiny A. Jackson; Vishnudas Sarda; Jaime E. Hart; Jaime E. Hart; Jorge E. Chavarro; Jorge E. Chavarro; et al. (Frontiers Media S.A., 2023)
IntroductionSupplements sold with claims to promote weight loss, cleansing/detoxing, increased energy, or boosted immunity can be dangerous, and consumers experiencing extreme stressors may be especially vulnerable to deceptive claims. The purpose of our study was to investigate associations of financial strain and psychological distress during the COVID-19 pandemic with use of supplements sold for weight loss, cleanse/detox, energy, or immunity.MethodsWe used repeated-measures data gathered over five survey waves from April/May 2020-April 2021 from the COVID-19 Substudy (N = 54,951), within three prospective US national cohorts (Nurses' Health Study 2, Nurses' Health Study 3, and Growing Up Today Study), to investigate longitudinal associations between financial strain and psychological distress and risk of use of potentially dangerous types of supplements. Surveys assessed use of supplements prior to and during the first year of the pandemic, as well as financial precarity, food insecurity, depressive and anxiety symptoms, perceived stress, and daily hassles. We fit sociodemographic-adjusted modified Poisson GEE models to estimate risk ratios (RRs) and 95% confidence intervals (CIs) for associations between baseline or lagged time-varying predictors and prevalent or incident (i.e., new-onset) use of each supplement type.ResultsAt baseline in April/May 2020, soon after pandemic onset, current use of supplement types was: weight loss 2.7%; cleanse/detox 3.2%; energy 4.4%; immune 22.6%. By the end of the study period, cumulative incidence was: weight loss 3.5%; cleanse/detox 3.7%; energy 4.5%; immune 21.3%. In prevalent-use analyses, financial precarity, food insecurity, and psychological distress were associated with up to 2.4 times the risk of use of these types of supplements across the study period. Similarly, in incident-use analyses, financial precarity and psychological distress were associated with up to 2.1 times the risk of initiating use; whereas, high food insecurity was associated with nearly 1.8 times higher risk of onset of weight-loss supplements use but was not associated with onset of use of other types of supplements.DiscussionWe found consistent evidence that during the first year of the pandemic, participants experiencing elevated financial strain and psychological distress were at heightened risk of initiating use of potentially dangerous types of supplements. Our findings raise concerns about deceptive claims about the safety and product effectiveness by manufacturers of these supplements to profit from vulnerable consumers during the pandemic.